Participation of ageing workers and their productivity in Malaysia labour market - Uma Murthy; Norehan Abdullah; Hussin Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2019)
The present study examined the participation of aging workers and their productivity in Malaysian labour market. A quantitative research approach is employed following the positivist assumption with a realist ontology and objectivist epistemology. Data was collected using a probabilistic sampling method, particularly a stratified random sampling technique. A questioner was distributed among 200 aging workers. The targeted population was older workers in private education and medical industries aging 55-60 years. The findings indicate that age discrimination, older workers’ intention to work after retirement, health status and education level influence participation of aging workers in Malaysia. Furthermore, few recommendations are put forward for employers to overcome these challenges.